The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.vas.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of health management practices and occupational health hazards in tiger shrimp (Penaeus monodon) and freshwater prawn (Macrobrachium rosenbergii) aquaculture in Bangladesh

Abstract: Diseases have been recognized as the major obstacle to the shrimp ( Penaeus monodon ) and prawn ( Macrobrachium rosenbergii ) aquaculture production in Bangladesh. This study provides an assessment of shrimp and prawn diseases/syndromes, health management practices, and occupational health hazards associated with the handling of chemical and biological products to prevent and treat shrimp and prawn diseases. A survey was conducted using a semi-structured questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The disease course observed in the farm for this study indicated that M. rosenbergii and M. nipponense have no tolerance to infection with DIV1. Many farms in Jiangsu, Guangdong, and Zhejiang Provinces [16,25], as well as in Southeast Asia [26,27] and Africa [28], have stocked ponds in polyculture mode with M. rosenbergii and P. vannamei or P. monodon . As M. rosenbergii has tolerance to infection with WSSV [21], the polyculture mode provides a profitable approach for farmers under the threat of WSSV.…”
Section: Discussionmentioning
confidence: 99%
“…The disease course observed in the farm for this study indicated that M. rosenbergii and M. nipponense have no tolerance to infection with DIV1. Many farms in Jiangsu, Guangdong, and Zhejiang Provinces [16,25], as well as in Southeast Asia [26,27] and Africa [28], have stocked ponds in polyculture mode with M. rosenbergii and P. vannamei or P. monodon . As M. rosenbergii has tolerance to infection with WSSV [21], the polyculture mode provides a profitable approach for farmers under the threat of WSSV.…”
Section: Discussionmentioning
confidence: 99%
“…Within these physical and economic constraints, the evidence from the survey and analysis suggests that farms benefited from improved seed, additional feed, and better management techniques (Ali et al., 2018). Untested seed sources were associated with increased mortality, while use of SPF and tested seed reduced incidence of shrimp diseases compared with untested sources.…”
Section: Discussionmentioning
confidence: 99%
“…Pursuing “disease‐free” farming within this socio‐economic arrangement positioned farmers into relations of production which made acts of desperation more rather than less likely. In contrast, and without underestimating the difficulties and room for improvement in food production practices, there is clear potential of polycultures and agro‐ecological forms of farming to reduce medicalisation by modulating risk experience and providing “insurance” in precarious physical and economic environments (Ali et al., 2018; Bush et al., 2010; Hanh & Boonstra, 2018), as well as generating environmental and nutritional gains (Shepon et al., 2020). Rather than being seen as barriers to disease management, these practices may be part of a raft of approaches to producing food in ways that are resilient and require low treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The disease course observed in the farm of this study indicated that M. rosenbergii and M. nipponense has no tolerance to the infection with SHIV. Many farms in Jiangsu, Guangdong, and Zhejiang Provinces [25,16], as well as in Southeast Asia [26,27] and Africa [28] have stocked ponds in polyculture mode with M. rosenbergii and P. vannamei or P. monodon. As M. rosenbergii has tolerance to infection with WSSV [21], the polyculture mode provides a profitable approach for farmers under the threat of WSSV.…”
Section: Discussionmentioning
confidence: 99%